Electrochemical method for loading adhesive polymer on surface of electrode and application

By using a combination of cyclic voltammetry and potential constant method in an electrochemical workstation, load-adhesive polymers are patterned on the surface of the array electrode, and the problems of short circuit and signal crosstalk between conductive adhesive layers in the array electrode are solved, achieving stable and accurate electrophysiological signal acquisition.

CN119595729AActive Publication Date: 2025-03-11SUZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411730715.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In array electrode application scenarios, mutual contact between conductive adhesive layers is prone to cause short circuits and signal crosstalk, and the prior art is difficult to achieve autonomous and selective loading of the adhesive layer, resulting in unstable skin-electrode interface.

Method used

By using a combination of cyclic voltammetry and potential constant method in an electrochemical workstation, the adhesive polymer is quickly and patterned in an inert gas environment, and the electrode surface is modified to form a conductive adhesive layer of micron thickness.

Benefits of technology

It achieves the effect of good electrode surface adhesion performance and low skin interface impedance, ensuring stability and accuracy when monitoring electrophysiological signals, and effectively avoiding short circuits and signal crosstalk.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595729A_ABST
    Figure CN119595729A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical method for loading adhesive macromolecules on the surface of an electrode and application, rapid and patterned loading of an adhesive layer can be realized by sequentially carrying out cyclic voltammetry and potentiostatic method, and the method has the characteristics of flexibility, simplicity and convenience in operation, wide application range and repeatability. According to the flexible array electrode modified by the electrochemical method provided by the invention, an adhesion layer is only obtained at a conductive part, so that the electrode has excellent adhesion performance and is more attached to the skin of a human body, and the stability of a skin-electrode interface is enhanced; when the electrode is attached to the skin for impedance testing, the skin interface impedance is lower than that of a commercial gel electrode, the monitored electrophysiological signals are stable and accurate, and meanwhile, short circuit and signal crosstalk can be effectively prevented due to the characteristic of the patterned load. The electrochemical method provided by the invention is used as a modification technology, is universal, simple and convenient for the electrophysiological sensor, and also has important significance for reducing the cost of wearable health monitoring equipment and improving the performance of the wearable health monitoring equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to an electrochemical method for loading adhesive polymers on an electrode surface and its application. Background Art

[0002] Electrophysiological sensors (electrodes) are used to collect complex electrophysiological signals and provide rich information about the body's condition. Reliable signal acquisition requires a stable skin-electrode interface to prevent adverse effects caused by interface changes. Although the introduction of the conductive adhesive layer enhances the stability of the interface to a certain extent, in the application scenario of the array electrode, the mutual contact between the conductive adhesive layers can easily cause short circuits and signal crosstalk.

[0003] Current research has explored several solutions to this technical difficulty of array electrodes, but all have limitations. For example, it may be difficult to ensure a stable connection by simply fixing the electrodes to the skin from the outside with tape or other adhesive materials, especially when the skin undergoes significant deformation. Another method is to manually drip gel on the surface of each sensing point of the array electrode to enhance contact with the skin. However, this method is not ideal for high-density and small-sized array electrodes. These solutions lack convenience and versatility, so there is an urgent need to develop a method that can autonomously and selectively load the adhesive layer. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an electrochemical method and application for loading adhesive polymers on the electrode surface. Cyclic voltammetry and constant potential method are performed in sequence to achieve rapid and patterned loading of the adhesion layer. This method has the characteristics of flexible and simple operation, wide application range and repeatability. The electrode modified by this electrochemical method has good adhesion performance and low skin interface impedance, and is stable and accurate when used to monitor electrophysiological signals.

[0005] The present invention is achieved through the following technical solutions:

[0006] The first aspect of the present invention provides an electrochemical method for loading an adhesive polymer on an electrode surface, comprising the following steps:

[0007] In an inert gas environment, a three-electrode electrochemical workstation was used to perform cyclic voltammetry (CV) and constant potential (FP) in sequence, and an adhesive polymer was loaded on the surface of the working electrode to obtain an electrode modified by an electrochemical method.

[0008] The electrochemical workstation comprises an electrochemical instrument, an electrolytic cell, a working electrode, a counter electrode, a reference electrode and an electrolyte, wherein the working electrode is a metal electrode or an array electrode, the metal electrode is a copper (Cu) electrode or a titanium (Ti) electrode, the array electrode is an array electrode containing copper and / or titanium, and the electrolyte comprises an imidazole ionic liquid, butyl acrylate (BA, ), an initiator, a chloride salt and an organic solvent; when the working electrode contains copper, the initiator is 4-bromobenzenediazonium tetrafluoroborate (BBD, ); when the working electrode contains titanium, the initiator is 4-bromobenzenediazonium tetrafluoroborate and 4-nitrobenzenediazonium tetrafluoroborate (NBD, ).

[0009] The electrochemical method (cyclic voltammetry and constant potential method) provided by the present invention can rapidly and regionally selectively modify metal electrodes or flexible array electrodes, realize rapid and patterned loading of the adhesion layer, and the operating device is reasonably designed and assembled simply. Among them, cyclic voltammetry (CV) and constant potential method (FP) are used for electrochemically controlled polymerization and grafting reactions on the conductive surface, combined with the significant conductivity difference between the flexible array electrode sensing point and the substrate material, which provides a theoretical basis for the selective loading of the polymer adhesion layer of the present invention.

[0010] The thickness of the adhesive polymer (adhesion layer) loaded on the surface of the working electrode of the present invention is in the micron level, wherein the butyl acrylate monomer provides adhesion, and the functional groups of the introduced ionic liquid provide sufficient conductivity, so that the metal electrode or the metal part of the flexible array electrode (i.e., the functional site, the sensing point) is given adhesion and can be reused and stored for a long time.

[0011] Furthermore, the array electrode is obtained by patterning and etching on a polyimide (PI) film using an electroplating method.

[0012] Furthermore, the electrolytic cell comprises a closing cover and air inlet and outlet pipes.

[0013] Furthermore, the working electrode (WE) is a copper sheet, a titanium sheet or a flexible array electrode, the counter electrode (CE) is a platinum wire electrode, and the reference electrode (RE) is a silver / silver chloride electrode.

[0014] Furthermore, the imidazole ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate (ILB, ) and / or 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide (ILN, ). Imidazole ionic liquid is used to provide ionic conductivity of the electrolyte.

[0015] Furthermore, the concentration of the imidazole ionic liquid in the electrolyte is 0.1-0.3 mol / L.

[0016] Furthermore, the volume of the butyl acrylate accounts for 45-55% of the volume of the electrolyte.

[0017] Furthermore, the chloride salt is potassium chloride (KCl) and / or sodium chloride (NaCl).

[0018] Furthermore, the organic solvent may be N,N-dimethylformamide (DMF, ).

[0019] Furthermore, the concentration of the initiator in the electrolyte is 15-25 mg / mL.

[0020] Furthermore, the electrolyte also includes vinyl ionic liquid.

[0021] Furthermore, the vinyl ionic liquid is selected from 1-vinyl-3-ethyl imidazole tetrafluoroborate (M1, )、1-vinyl-3-butyl imidazole tetrafluoroborate (M2, )、1-vinyl-3-ethylimidazolium trifluoromethanesulfonyl imide salt (M3, ) and 1-vinyl-3-butyl imidazole trifluoromethanesulfonyl imide salt (M4, ) one or more of the following.

[0022] Furthermore, the volume ratio of the butyl acrylate to the vinyl ionic liquid is 1:(1-2).

[0023] Furthermore, the total volume of the butyl acrylate and the vinyl ionic liquid accounts for 45-55% of the volume of the electrolyte.

[0024] Furthermore, the cyclic voltammetry is for electrochemical reduction of diazonium salt to obtain phenyl radicals.

[0025] In a specific embodiment, an electrochemical workstation is used to perform a pre-scan (cyclic voltammetry, scan rate of 0.1-0.2 V·s) under an inert environment. -1 , one cycle, vs RE) to obtain the initiation characteristics and electrochemical curves of the initiator. According to the electrochemical curves, the reduction peak position range was determined and a low-rate scan was performed (cyclic voltammetry, the scan rate was 0.01-0.02 V·s -1 , multiple cycles, vs RE).

[0026] Furthermore, during the constant potential method, phenyl radicals induce polymerization and chain entanglement of monomers.

[0027] In a specific embodiment, a suitable potential (corresponding to the potential at the end of the reduction peak in the last cycle of cyclic voltammetry) is selected to perform a constant reduction potential treatment (constant potentiostat, 1-4 hours, vs RE).

[0028] In a specific embodiment, after the reaction is completed, the working electrode is taken out, the surface is rinsed and dried to obtain a metal electrode or a flexible array electrode modified by an electrochemical method.

[0029] Furthermore, the inert gas may be nitrogen, argon, etc. The electrochemical modification can only achieve effective loading of the adhesion layer if it is performed in an inert environment.

[0030] In a specific embodiment, after the electrolyte is prepared, an inert gas is continuously blown into the electrolytic cell to expel oxygen (20-30 minutes), and then the gas path is sealed to maintain an inert environment in the electrolytic cell.

[0031] In a specific embodiment, the two steps of the electrochemical modification method of the present invention (cyclic voltammetry and constant potential method) need to be performed sequentially to achieve effective loading of the adhesion layer. If only one of the steps is performed, effective loading cannot be achieved.

[0032] In a specific embodiment, the adhesion layer of the electrode modified by the electrochemical method provided by the present invention will be more or less damaged after use, but the remaining adhesion layer can continue to be used; if the adhesion layer fails after multiple uses, the adhesion layer can be washed off with ethanol and a secondary modification can be performed to obtain the adhesion layer again.

[0033] The second aspect of the present invention provides an electrochemically modified electrode prepared by the electrochemical method described in the first aspect.

[0034] The third aspect of the present invention provides an application of the electrode modified by the electrochemical method described in the second aspect in electrophysiological signal collection.

[0035] The flexible array electrode modified by the electrochemical method provided by the present invention only obtains an adhesion layer at the sensing point. When the electrode is attached to the skin for impedance testing, the skin interface impedance is greatly reduced and is lower than that of commercial gel electrodes. At the same time, the flexible array electrode modified by the electrochemical method provided by the present invention can stably and accurately measure electrocardiographic signals (ECG) and electromyographic signals (EMG), and effectively avoid signal crosstalk between sub-electrode sensing points.

[0036] Beneficial effects of the present invention:

[0037] The present invention provides an electrochemical method for loading adhesive polymers on the surface of an electrode, which can selectively load adhesive polymers on the surface area of ​​a flexible array electrode, thereby solving the shortcomings in the prior art. The present invention sequentially performs two steps, cyclic voltammetry and constant potential method, to achieve rapid and patterned loading of an adhesive layer. The method has the characteristics of flexible and simple operation, wide application range, and repeatability.

[0038] The flexible array electrode modified by the electrochemical method provided by the present invention only obtains an adhesion layer at the conductive part, so that the electrode has excellent adhesion performance, fits the human skin better, and enhances the stability of the skin-electrode interface; when it is attached to the skin for impedance testing, the skin interface impedance is lower than that of the commercial gel electrode, and the monitored electrophysiological signal is stable and accurate. At the same time, the characteristics of the patterned load enable it to effectively prevent short circuits and signal crosstalk. The electrochemical method provided by the present invention is used as a modification technology, which is both universal and simple for electrophysiological sensors, and is also of great significance for reducing the cost of wearable health monitoring equipment and improving its performance.

[0039] The electrochemical method provided by the present invention is expected to be extended to more complex electrode systems, such as stretchable electrodes, microelectrode arrays and breathable electrodes, and become a universal patterning strategy to solve the breathability problem of skin electrodes and the signal crosstalk problem in array electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic diagram of the electrolytic cell apparatus used in the present invention.

[0041] Figure 2 The present invention provides a reaction flow chart of the electrochemical method.

[0042] Figure 3 Schematic diagram of the flexible array electrode before and after electrochemical modification.

[0043] Figure 4 The figures are a physical picture of the flexible array electrode containing copper in Example 1 and a microscopic morphology picture after electrochemical modification; wherein, (a) is a physical picture of the flexible array electrode containing copper, and (b) is a scanning electron microscope picture of the flexible array electrode modified by the electrochemical method obtained in Example 1.

[0044] Figure 5 The figures and actual pictures are the lap shear strength diagrams of the metal sheet modified by the electrochemical method and PDMS obtained in Examples 4, 5 and Comparative Examples 5, 6; wherein, (a) is the lap shear strength diagram of the metal electrode modified by the electrochemical method and PDMS obtained in Examples 4, 5 and Comparative Examples 5, 6, and (b) is the actual picture of the metal electrode modified by the electrochemical method obtained in Example 5 and Comparative Examples 5, 6.

[0045] Figure 6 This is the lap shear strength diagram of the copolymers obtained by four vinyl ionic liquids (M1 / M2 / M3 / M4) and butyl acrylate (BA) under thermal initiation of azobisisobutyronitrile (AIBN) evenly applied on two pieces of PDMS.

[0046] Figure 7 The skin interface impedance diagrams of the flexible array electrode modified by electrochemical method obtained in Examples 1-3, the unmodified flexible array electrode (fixed with tape) and the commercial gel electrode.

[0047] Figure 8 Schematic diagram of the flexible array electrode modified by the electrochemical method (electrochemically modified electrode) obtained in Example 3, the flexible array electrode not modified by the electrochemical method (electrode fixed with tape) and the flexible array electrode modified by commercial gel spot coating (commercial gel spot coating modified electrode) for measuring electrocardiogram signals and the measured electrocardiogram; wherein (a) is a schematic diagram of the electrode attached to the human chest for measuring electrocardiogram signals, and (b) is a schematic diagram of the measured electrocardiogram and the signal crosstalk occurring during the commercial gel spot coating process.

[0048] Fig. 9 The flexible array electrode modified by the electrochemical method (electrochemically modified electrode) obtained in Example 3, the flexible array electrode not modified by the electrochemical method (electrode fixed with tape) and the flexible array electrode modified by commercial gel spot coating (commercial gel spot coating modified electrode) are used to measure electromyographic signals and the measured electromyograms; wherein (a) is a schematic diagram of being attached to a human arm for measuring electromyographic signals, and (b) is a schematic diagram of the measured electromyogram and the signal crosstalk occurring during the commercial gel spot coating process. DETAILED DESCRIPTION

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0050] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0051] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0052] The present invention provides an electrochemical method for loading an adhesive polymer on an electrode surface, comprising the following steps:

[0053] In an inert gas environment, a three-electrode electrochemical workstation was used to perform cyclic voltammetry (CV) and constant potential (FP) in sequence, and an adhesive polymer was loaded on the surface of the working electrode to obtain an electrode modified by an electrochemical method.

[0054] The electrochemical workstation comprises an electrochemical instrument, an electrolytic cell, a working electrode, a counter electrode, a reference electrode and an electrolyte, wherein the working electrode is a metal electrode or an array electrode, the metal electrode is a copper (Cu) electrode or a titanium (Ti) electrode, the array electrode is an array electrode containing copper and / or titanium, and the electrolyte comprises an imidazole ionic liquid, butyl acrylate (BA, ), an initiator, a chloride salt and an organic solvent; when the working electrode contains copper, the initiator is 4-bromobenzenediazonium tetrafluoroborate (BBD, ); when the working electrode contains titanium, the initiator is 4-bromobenzenediazonium tetrafluoroborate and 4-nitrobenzenediazonium tetrafluoroborate (NBD, ).

[0055] Preferably, the electrolytic cell is a three-electrode electrochemical electrolytic cell, comprising a closed cover and an inlet and outlet gas pipe, and the electrolytic cell device is as follows Figure 1 As shown; there are no specific requirements or special limitations on the brands and models of other devices.

[0056] In a specific embodiment, the working electrode (WE) is a copper sheet, a titanium sheet or a flexible array electrode, the counter electrode (CE) is a platinum wire electrode, and the reference electrode (RE) is a self-made silver / silver chloride electrode. The specifications and purity of the metal sheet and the brand and purity of the platinum wire electrode are not specifically required or specially limited.

[0057] Preferably, the flexible array electrode is a PI electrode with a thickness of 17 or 35 μm copper, which is obtained by patterning and etching using an electroplating method. The pattern of the flexible array electrode is for the convenience of practical application and can be changed without special significance.

[0058] In a specific embodiment, the first step of the electrochemical method is cyclic voltammetry, i.e., multiple cycles (ten cycles), low rate (0.01-0.02 V s -1 ) cyclic voltammetry scans (CV Cycles). Under electrochemical reduction, the phenyl radicals obtained by the reduction of the initiator will bind to the metal, and the free radicals will generate initiation sites on the grafted group by absorbing hydrogen atoms, and then a thin layer of dendritic polymer layer (nanoscale) will be grafted on the metal surface. Generally, a pre-scan (0.1-0.2V s -1) to determine the potential range where the reduction peak appears (the reduction peak corresponds to the reaction of phenyldiazonium salt reducing to produce phenyl radicals). Then a low-rate scan is performed within the selected voltage range. In the next few cycles, it can be found that the reduction peak moves to the low voltage region, which is due to the increase in the resistance of the grafted polymer.

[0059] In a specific embodiment, the second step of the electrochemical method is a constant potential method (FP), that is, a fixed reduction potential treatment is performed for a long time. Generally, the voltage corresponding to the end of the reduction peak in the last cycle of low-rate scanning is selected for a long time (1-4h) of constant reduction potential treatment. In this step, the main reaction is the polymerization of monomers in the solution near the cathode. As the FP time increases, the current shows a downward trend, indicating that the polymer grown on the cathode surface causes an increase in resistance. During the FP polymerization process, the chain entanglement between the polymer in the solution and the grafted chain causes the thickness of the grafted polymer layer to increase significantly, reaching the micron level.

[0060] Figure 2 A reaction flow chart of the electrochemical method provided by the present invention, Figure 3 Schematic diagram of the flexible array electrode before and after electrochemical modification.

[0061] The present invention adopts electrochemical modification method and only needs to perform cyclic voltammetry and constant potential method in sequence to complete the patterning of the metal sheet or flexible array electrode adhesion layer, and selectively modifies the micron-level thick conductive adhesion layer region to the sensing point of the flexible array electrode.

[0062] In the following embodiments and comparative examples, the silver / silver chloride electrode was prepared by the following method: prepared by electrochemical corrosion, wherein the working electrode (WE) was a silver wire; the counter electrode (CE) was a platinum wire electrode; the reference electrode (RE) was a commercial silver / silver chloride electrode; the electrolyte was a 1 mol / L hydrochloric acid solution; the working electrode silver wire became a homemade silver / silver chloride electrode under electrochemical constant potential corrosion, wherein the voltage was 0.5 V and the time was 30 s.

[0063] Example 1

[0064] An electrochemical method for loading an adhesive polymer on the surface of a flexible array electrode containing copper comprises the following steps:

[0065] (1) Preparation of electrolyte: The solvent is a DMF solution containing saturated KCl, to which 0.1 mol / L ILB is added, BA is added as a monomer (the volume of the monomer accounts for 50% of the total volume of the solution), and finally 20 mg / mL BBD is added as an initiator.

[0066] (2) The flexible array electrode was used as the working electrode, the Pt wire electrode was used as the counter electrode, and the homemade silver / silver chloride electrode was used as the reference electrode. The electrodes were installed in a closed electrolytic cell. Oxygen was expelled by continuously blowing N2 into the closed electrolytic cell (20 min), and then the gas path was sealed to maintain an inert gas environment in the electrolytic cell.

[0067] (3) Perform a pre-scan using cyclic voltammetry on an electrochemical workstation at 0.1 V s -1 , one cycle, lock the position of the reduction peak, and perform low-rate cyclic voltammetry, 0.01V s -1 , ten cycles.

[0068] (4) After the cyclic voltammetry is completed, the potential corresponding to the end of the reduction peak in the last cycle is selected and the constant potential method is performed for 2 hours.

[0069] (5) After the constant potential method is completed, the flexible array electrode is taken out, its surface is rinsed with ethanol and dried to obtain a flexible array electrode modified by an electrochemical method.

[0070] Figure 4 The figures are a physical picture of the flexible array electrode containing copper in Example 1 and a microscopic morphology picture after electrochemical modification; wherein, (a) is a physical picture of the flexible array electrode containing copper, and (b) is a scanning electron microscope picture of the flexible array electrode modified by the electrochemical method obtained in Example 1. The microscopic morphology of the adhesion layer on the surface of the flexible array electrode can be clearly observed under the scanning electron microscope.

[0071] Example 2

[0072] An electrochemical method for loading an adhesive polymer on the surface of a flexible array electrode containing copper is basically the same as the electrochemical method of Example 1, except that: in step (1), 0.1 mol / L ILB is replaced by 0.1 mol / L ILN; the monomers are BA and M4, the volume ratio is 1:1, and the total volume of the monomers accounts for 50% of the total volume of the solution.

[0073] Example 3

[0074] An electrochemical method for loading an adhesive polymer on the surface of a flexible array electrode containing copper is basically the same as the electrochemical method of Example 1, except that: in step (1), 0.1 mol / L ILB is replaced by 0.1 mol / L ILN; the monomers are BA and M4, the volume ratio is 1:2, and the total volume of the monomers accounts for 50% of the total volume of the solution.

[0075] Example 4

[0076] An electrochemical method for loading an adhesive polymer on a Ti sheet surface comprises the following steps:

[0077] (1) Preparation of electrolyte: The solvent is a DMF solution containing saturated KCl, to which 0.1 mol / L ILB is added, BA is added as a monomer (the volume of the monomer accounts for 50% of the total volume of the solution), and finally 10 mg / mL BBD and 10 mg / mL NBD are added as initiators.

[0078] (2) A Ti sheet was used as the working electrode, a Pt wire electrode was used as the counter electrode, and a homemade silver / silver chloride electrode was used as the reference electrode. The electrodes were installed in a closed electrolytic cell. Oxygen was expelled by continuously blowing N2 into the closed electrolytic cell (20 min), and then the gas path was sealed to maintain an inert gas environment in the electrolytic cell.

[0079] (3) Perform a pre-scan using cyclic voltammetry on an electrochemical workstation at 0.1 V s -1 , one cycle, lock the position of the reduction peak, and perform low-rate cyclic voltammetry, 0.01V s -1 , ten cycles.

[0080] (4) After the cyclic voltammetry is completed, the potential corresponding to the end of the reduction peak in the last cycle is selected and the constant potential method is performed for 2 hours.

[0081] (5) After the constant potential method is completed, the Ti sheet is taken out, its surface is rinsed with ethanol and dried to obtain a Ti electrode modified by an electrochemical method.

[0082] Example 5

[0083] An electrochemical method for loading an adhesive polymer on a Cu sheet surface comprises the following steps:

[0084] (1) Preparation of electrolyte: The solvent is a DMF solution containing saturated KCl, to which 0.1 mol / L ILB is added, BA is added as a monomer (the volume of the monomer accounts for 50% of the total volume of the solution), and finally 20 mg / mL BBD is added as an initiator.

[0085] (2) A Cu sheet was used as the working electrode, a Pt wire electrode was used as the counter electrode, and a homemade silver / silver chloride electrode was used as the reference electrode. The electrodes were installed in a closed electrolytic cell. Oxygen was expelled by continuously blowing N2 into the closed electrolytic cell (20 min), and then the gas path was sealed to maintain an inert gas environment in the electrolytic cell.

[0086] (3) Perform a pre-scan using cyclic voltammetry on an electrochemical workstation at 0.1 V s -1 , one cycle, lock the position of the reduction peak, and perform low-rate cyclic voltammetry, 0.01V s -1 , ten cycles.

[0087] (4) After the cyclic voltammetry is completed, the potential corresponding to the end of the reduction peak in the last cycle is selected and the constant potential method is performed for 2 hours.

[0088] (5) After the constant potential method is completed, the Cu sheet is taken out, its surface is rinsed with ethanol and dried to obtain a Cu electrode modified by an electrochemical method.

[0089] Comparative Example 1

[0090] An electrochemical method for loading an adhesive polymer on the surface of a flexible array electrode containing copper is basically the same as the electrochemical method of Example 1, except that in step (1), 20 mg / mL of BBD is replaced by 20 mg / mL of NBD.

[0091] Comparative Example 2

[0092] An electrochemical method for loading an adhesive polymer on the surface of a flexible array electrode containing copper is basically the same as the electrochemical method of Example 1, except that in step (1), 20 mg / mL of BBD is replaced by 10 mg / mL of BBD and 10 mg / mL of NBD.

[0093] Comparative Example 3

[0094] An electrochemical method for loading an adhesive polymer on the surface of a Ti sheet is basically the same as the electrochemical method of Example 4, except that in step (1), 10 mg / mL of BBD and 10 mg / mL of NBD are replaced with 20 mg / mL of BBD.

[0095] Comparative Example 4

[0096] An electrochemical method for loading an adhesive polymer on the surface of a Ti sheet is basically the same as the electrochemical method of Example 4, except that in step (1), 10 mg / mL of BBD and 10 mg / mL of NBD are replaced with 20 mg / mL of NBD.

[0097] Comparative Example 5

[0098] An electrochemical method for loading an adhesive polymer on a Cu sheet surface is substantially the same as the electrochemical method of Example 5, except that the constant potential method of step (4) is not performed.

[0099] Comparative Example 6

[0100] An electrochemical method for loading an adhesive polymer on a Cu sheet surface is substantially the same as the electrochemical method of Example 5, except that the cyclic voltammetry of step (3) is not performed.

[0101] The electrodes modified by the electrochemical method obtained in Examples 1-4 and Comparative Examples 1-4 were subjected to a viscosity test. The test method was: a weighing paper was pressed on the electrode modified by the electrochemical method. If the electrode did not fall off when the weighing paper was pulled, the result was considered to be sticky. The test results are shown in Table 1:

[0102] Table 1

[0103]

[0104]

[0105] The shear strength was tested by a universal materials testing machine in tensile mode at a shear rate of 60 mm / min on an electrochemically modified metal sheet bonded to a polydimethylsiloxane film (PDMS).

[0106] Figure 5 The figures and physical pictures of the lap shear strength of the metal sheet modified by the electrochemical method and PDMS obtained in Examples 4, 5 and Comparative Examples 5 and 6; (a) is the lap shear strength figure of the metal electrode modified by the electrochemical method and PDMS obtained in Examples 4, 5 and Comparative Examples 5 and 6, and (b) is the physical picture of the metal electrode modified by the electrochemical method obtained in Example 5 and Comparative Examples 5 and 6. Figure 5 As can be seen in (a), the lap shear strength between the electrochemically modified Cu sheet and the PDMS film is about 3.03 kPa, and the lap shear strength between the electrochemically modified Ti sheet and the PDMS film is about 5.22 kPa. Figure 5 In (b), we can see the growth conditions of the surface of the metal sheet modified by the electrochemical method. When only CV is performed, no adhesion layer grows on the surface of the metal sheet, and it is non-sticky; when only FP is performed, the adhesion layer does not grow on the surface of the metal sheet and falls off in the solution; after CV and FP, an adhesion layer obviously grows on the surface of the metal sheet, and it is sticky.

[0107] Figure 6 This is the lap shear strength diagram of the copolymers obtained by four vinyl ionic liquids (M1 / M2 / M3 / M4) and butyl acrylate (BA) under thermal initiation of azobisisobutyronitrile (AIBN) evenly applied on two pieces of PDMS.

[0108] The skin interface impedance was measured by the controlled potential EIS (impedance technology) of the electrochemical workstation, with a measurement range of 10kHz to 10Hz and an amplitude of 0.2V RMS. The electrochemical impedance was measured by the flexible array electrode modified by the electrochemical method, where the center distance between the two main working sub-electrodes in the flexible array electrode was about 1.6cm, and the skin contact area of ​​each sub-electrode was about 0.2cm 2; For comparison, the contact area between each commercial gel electrode and the skin is 0.785 cm 2 , the distance between the two commercial gel electrodes was kept about 1.6 cm.

[0109] Figure 7 The skin interface impedance diagrams of the flexible array electrode modified by electrochemical method, the unmodified flexible array electrode (fixed with tape) and the commercial gel electrode obtained in Examples 1-3 are shown in FIG. Figure 7 It can be seen that the skin interface impedance of the flexible array electrode modified by the electrochemical method is greatly reduced. In a wider frequency range, the skin interface impedance per unit area of ​​the flexible array electrode modified by the electrochemical method is better than that of the commercial gel electrode.

[0110] The flexible array electrode modified by the electrochemical method obtained in Example 3 (electrochemically modified electrode), the flexible array electrode not modified by the electrochemical method (electrode fixed with tape) and the commercial gel spot modified electrode (commercial gel spot modified electrode) were used to measure electrocardiogram (ECG) and electromyogram (EMG) signals. The ECG and EMG signals were recorded by a Backyard Brains Spiker Box with three electrodes. The signal-to-noise ratio of the flexible array electrode coated with commercial gel spot was 11.01 dB, and the signal-to-noise ratio of the flexible array electrode modified by the electrochemical method was 11.69 dB.

[0111] Figure 8 Schematic diagram of the flexible array electrode modified by the electrochemical method obtained in Example 3, the flexible array electrode not modified by the electrochemical method (fixed with tape) and the flexible array electrode modified by commercial gel spot coating for measuring electrocardiogram signals and the measured electrocardiogram; wherein (a) is a schematic diagram of the electrode attached to the human chest for measuring electrocardiogram signals, and (b) is a schematic diagram of the measured electrocardiogram and the signal crosstalk occurring during the commercial gel spot coating process.

[0112] Fig. 9 Schematic diagram of the flexible array electrode modified by the electrochemical method obtained in Example 3, the flexible array electrode not modified by the electrochemical method (fixed with tape) and the flexible array electrode modified by commercial gel spot coating for measuring electromyographic signals and the measured electromyogram; wherein, (a) is a schematic diagram of the flexible array electrode attached to a human arm for measuring electromyographic signals, and (b) is a schematic diagram of the measured electromyogram and the signal crosstalk occurring during the commercial gel spot coating process.

[0113] from Figure 8 and Fig. 9It can be seen that the flexible array electrodes modified by electrochemical methods can stably and accurately measure ECG and EMG signals. The measured electrophysiological signals are not only comparable to those of the flexible array electrodes modified by commercial glue coating, but also effectively avoid signal crosstalk between sub-electrode sensing points during the coating process.

[0114] In summary, the present invention provides an electrochemical method for selectively loading adhesive polymers on the surface of a flexible electrode, utilizing the conductivity difference between the flexible electrode sensing point and the substrate material to achieve regional selective loading of adhesive and ion conductive polymers through in-situ electrochemical reactions, thereby achieving patterning of the adhesive layer. The electrochemical method provided by the present invention requires two steps (CV and FP) to be performed sequentially to achieve rapid and selective modification of the electrode surface, and the thickness of the modified adhesive layer is in the micron level. In the modified adhesive layer system, the butyl acrylate monomer provides viscosity, and the functional groups of the introduced ionic liquid provide sufficient conductivity.

[0115] The flexible array electrode modified by the electrochemical method provided by the present invention only loads an effective adhesion layer at the sensing point, thereby improving the stability of the skin-electrode interface and the quality of electrophysiological signal acquisition, and effectively avoiding signal crosstalk between the sensing points of the flexible array electrode; in addition, the flexible electrode modified by the electrochemical method can be reused and stored for a long time, and the performance of the adhesion layer will not degrade; even if the adhesion layer fails, the adhesion layer can be cleaned for secondary modification; the electrochemical method modification method is also applicable to the construction of the adhesion layer of metal sheets (such as Cu or Ti). The electrochemical method for selectively loading adhesion polymers on the surface area of ​​the flexible electrode provided by the present invention is applicable to metal sheets and flexible array electrodes, and has the characteristics of reasonable reaction device design, simple operation method, wide application range, repeatability, low modification cost and high success rate.

[0116] The electrochemical method provided by the present invention is expected to be extended to more complex electrode systems, such as stretchable electrodes, microelectrode arrays and breathable electrodes, and become a universal patterning strategy to solve the breathability problem of skin electrodes and the signal crosstalk problem in array electrodes.

[0117] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An electrochemical method for loading an adhesive polymer on an electrode surface, characterized in that: The following steps are involved: In an inert gas environment, a three-electrode electrochemical workstation was used to perform cyclic voltammetry and constant potential method in sequence, and an adhesive polymer was loaded on the surface of the working electrode to obtain an electrode modified by an electrochemical method. The electrochemical workstation comprises an electrochemical instrument, an electrolytic cell, a working electrode, a counter electrode, a reference electrode and an electrolyte. The working electrode is a metal electrode or an array electrode. The metal electrode is a copper electrode or a titanium electrode. The array electrode is an array electrode containing copper and / or titanium. The electrolyte comprises an imidazole ionic liquid, butyl acrylate, an initiator, a chloride salt and an organic solvent. When the working electrode contains copper, the initiator is 4-bromobenzenediazonium tetrafluoroborate. When the working electrode contains titanium, the initiator is 4-bromobenzenediazonium tetrafluoroborate and 4-nitrobenzenediazonium tetrafluoroborate.

2. The electrochemical method according to claim 1, characterized in that The imidazolium ionic liquid is 1-ethyl-3-methylimidazolium tetrafluoroborate and / or 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide.

3. The electrochemical method according to claim 1, characterized in that The concentration of the imidazole ionic liquid in the electrolyte is 0.1-0.3 mol / L.

4. The electrochemical method according to claim 1, characterized in that The electrolyte also includes a vinyl ionic liquid.

5. The electrochemical method according to claim 4, characterized in that The vinyl ionic liquid is selected from one or more of 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-vinyl-3-butylimidazolium tetrafluoroborate, 1-vinyl-3-ethylimidazolium trifluoromethanesulfonyl imide and 1-vinyl-3-butylimidazolium trifluoromethanesulfonyl imide.

6. The electrochemical method according to claim 4, characterized in that The total volume of the butyl acrylate and the vinyl ionic liquid accounts for 45-55% of the volume of the electrolyte.

7. The electrochemical method according to claim 1, characterized in that The specific operation of the cyclic voltammetry method is: -1 A pre-scan was performed at a scanning rate of 0.01-0.02 V·s -1 Scan multiple cycles at a scan rate.

8. The electrochemical method according to claim 7, characterized in that The specific operation of the constant potential method is: the potential at the end of the reduction peak in the last cycle of the cyclic voltammetry is subjected to a constant reduction potential treatment.

9. An electrode modified by an electrochemical method, characterized in that: Prepared by the electrochemical method described in any one of claims 1 to 8.

10. Use of the electrode modified by the electrochemical method according to claim 9 in electrophysiological signal collection.

Citation Information

Patent Citations

  • Electropolymerization of a coating onto an electrode material

    CN104937146A

  • Electrochemical detection kit for high-sensitivity detection of AFB1 based on eRAFT aggregation signal amplification strategy and application

    CN116008369A

  • Method for grafting and growing a conductive organic film on a surface

    CN1578705A

  • Electropolymerization of a coating onto an electrode material

    US20140173889A1

  • Method for grafting and growing a conductive organic film on a surface

    WO2003018212A1